2020
DOI: 10.7759/cureus.11845
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study on Rapidly Declining SARS‐CoV‐2 IgG Antibodies Within One to Three Months of Testing IgG Positive: Can It Lead to Potential Reinfections?

Abstract: Background COVID-19 immunoglobulin G (IgG) antibodies have been considered to provide protective immunity and its immunoassays have been widely used for serosurveillance. In our serosurveillance on an industrial workforce of randomly selected 3296 subjects, COVID-19 IgG antibody positivity was reported in 7.37% (243) subjects. However, when 30 days later, eight of the 243 COVID-19 IgG antibody-positive individuals complained of symptoms suggestive of COVID-19 infection and were confirmed as COVID-19 infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 14 publications
1
22
0
2
Order By: Relevance
“…The other important question is whether HCWs with previous infection or measurable antibodies are immune to reinfections and hence, can be deployed in high-risk areas [11]. While some initial studies have shown that 40% of asymptomatic subjects and 12.9% of symptomatic subjects became seronegative for IgG antibodies in the "early convalescent phase", there are other isolated reports of rapid decay of IgG antibodies in persons with mild infection [21][22][23][24]. The longevity of the immune response and the level of neutralizing antibodies needed for protection remain unclear, as cases of relapse/reinfection with SARS-CoV-2 have been reported [21].…”
Section: Discussionmentioning
confidence: 99%
“…The other important question is whether HCWs with previous infection or measurable antibodies are immune to reinfections and hence, can be deployed in high-risk areas [11]. While some initial studies have shown that 40% of asymptomatic subjects and 12.9% of symptomatic subjects became seronegative for IgG antibodies in the "early convalescent phase", there are other isolated reports of rapid decay of IgG antibodies in persons with mild infection [21][22][23][24]. The longevity of the immune response and the level of neutralizing antibodies needed for protection remain unclear, as cases of relapse/reinfection with SARS-CoV-2 have been reported [21].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, IgM, IgG and nAb titres peak ~ 2–3 weeks post-symptom onset and decline to undetectable levels by 6 weeks for IgM, whereas IgG and nAb reach a plateau before declining within 2–3 months (Fig. 1 b) [ 6 , 55 57 ]. Mathematical modelling estimates that within 1 year IgG antibodies to nucleocapsid, spike protein and RBD wane to 7%, 36% and 31% of their titres at 2 weeks post-symptom onset, respectively [ 58 ].…”
Section: Antibody Waning In Coronavirus Infectionsmentioning
confidence: 99%
“…(17 -20) The longevity of the immune response and the level of neutralizing antibodies needed for protection remain unclear, as cases of relapse/reinfection with SARS-CoV-2 have been reported. (17) The variation in the immune response could be attributed to the symptomatology, being less in milder infections, the constitution of individuals, or nutritional status. (21) Thus, further studies are needed to better understand the possible relationship between these factors and variation in the development of antibodies.…”
Section: Discussionmentioning
confidence: 99%